DESIGNING MATHEMATICS PROBLEM BASED ON PISA TASK USING THE ETHNOMATHEMATICS CONTEXT - Andi Dian Angriani (International Conference on Social and Islamic Studies, 2021)
This study aims to determine the procedure and to assess the quality of developing mathematical problems using the ethnomathematics context. The research method used is design research with the type of development study. The outcomes of this research were mathematical problems using the ethnomathematics context, which measured mathematics literacy ability. The content validity results based on the validator indicated that the test items were valid after being assessed using the Content Validity Ratio (CVR) and Content Validity Index (CVI). In the reliability test, the mathematics problem using the ethnomathematics context was reliable. Based on the results of the analysis obtained, the average ability of literacy of the students are in the medium category. Therefore, the development PISA like mathematics problems using the ethnomathematics context as a learning resource can facilitate students learning mathematics.